Advocate's Responsibility In Defending Clients Based On Islamic Perspective - Fauziah Lubis; Dinda Tazkia Aulia; Cindy Dinda Putri; Cika Audira; Eko Abdi Pranata; Dewi Seftiana Andriani (Fox Justi : Jurnal Ilmu Hukum, 2025)
Advocates are one of the key pillars in upholding the law, serving as a bridge between society and the judicial system. From an Islamic perspective, justice is a fundamental value that must be upheld in every action, including in the practice of advocacy. This study aims to examine the responsibilities of advocates in defending clients based on the Islamic perspective and to analyze the legal consequences for advocates who fail to defend clients with fairness, honesty, and truthfulness. The method used in this research is normative juridical. The study reveals that advocates in Islam are responsible for upholding justice ('adl) in accordance with Sharia principles. Their defense must be based on the values of truth (haqq), without manipulating facts or defending unjust cases. Advocates who violate these principles are not only at risk of facing legal sanctions under the law but also bear spiritual consequences in the form of grave sins. In Islam, justice is not merely procedural but also substantial, emphasizing balance, honesty, and moral integrity. This study recommends strengthening regulations, raising awareness of Islamic values, and integrating Islamic principles of justice into advocacy practices to ensure that the profession contributes to achieving true justice, both in this world and in the hereafter.